CLOTHING SALES STRATEGY AT ANEKATEX SHOP WITH E-CRM CONCEPT - Pratiwi, Winda; Amin, Muhammad; Putri, Pristiyanilicia (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Toko Anekatex is a business engaged in fashion for women, men, children, as well as school uniforms, pajamas, and other robes located on Jalan Dr. Sutomo No. 41 Kisaran city. In maintaining more advanced competitiveness, the company must continue to develop technology, another thing that needs to be considered in making the company more advanced is the relationship with customers which is also an important thing to always maintain. In an effort to manage good relationships with potential customers and customers, companies use Customer Relationship Management (CRM). CRM is a service to customers that is personal, with the aim of providing consistent experience, so that it can provide customer satisfaction, and also get good relationships in the long term. By implementing a good E-CRM, companies will more easily interact with potential customers and customers and provide information according to their needs Customers can also obtain the information they need more quickly and easily. By implementing Customer Relationship Management (CRM) carried out at Anekatex Stores as an effort to improve customer strategies are well proven by the series of processes above and with this application to increase buybacks from total sales every month.